CLINICAL AND BACTERIOLOGICAL PECULIARITIES OF THE ACUTE OTITES MEDIA IN CHILDREN OF 0–5 YEARS OF AGE: PROVISIONAL DATA - A. L. Perova; A. A. Ruleva; S. S. Belanov; S. M. Kharit; S. V. Sidorenko (Педиатрическая фармакология, 2012)
Analysis of clinical peculiarities and etiological structure of otites in 150 children of 0–5 years of age hospitalized with the diagnosis «acute otitis media», which was proved otoscopically and at paracentesis, was conducted. Fluid obtained at paracentesis was examined bacteriologically — in 128 cases, by the PCR method — in 129 cases. 121 disease cases were etiologically identified, pneumococcus was singled out in 93 children (76.9%), as the only causative agent — in 31.4%, in combination with other pathogens — in 45.5%. Pneumococcal serotyping showed that the singled out strains correspond to the pneumococcal infection conjugate vaccines registered in Russia, which is a reason for cohort immunization of small children.